Музейна педагогіка: інноваційна технологія інтелектуального розвитку - Маньковська, Р. (Краєзнавство, 2019)
У статті висвітлюється проблема розвитку музейної педагогіки як освітньо-музейної технології для інтелектуального розвитку підростаючого покоління, простежено формування музейних підходів до навчального процесу в історичному контексті та, через зіставлення зарубіжного і українського досвіду, виділено особливості взаємодії освітньої та музейної галузей в Україні. Приділено увагу сучасним формам та методам освітньо-виховного процесу в музейному середовищі, актуальним освітньо-музейним проектам і перспективам музейної педагогіки. The article deals with the problem of the development of museum pedagogy as an educational and museum technology for the intellectual development of the younger generation. It traces the formation of museum approaches to the educational process in the historical context and, by comparing foreign and Ukrainian experience, the article highlights the interaction between the educational and museum branches in Ukraine. Also, the attention is paid to modern forms and methods of educational process in the museum environment, current educational and museum projects and perspectives of museum pedagogy. The urgency of examining the problem is caused by the growing social role of museums as a socio-cultural institute, the importance of developing the theoretical foundations of museum pedagogy as a scientific discipline, the emergence and implementation of special museum-educational programs for the younger generation and the formation of museum culture. As an educational-museum model of the educational process, museum pedagogy applies systematic, visual, scientific and accessible pedagogical principles. An important place in the article is given to museums in an educational institution, which can be considered as a creative laboratory for personality development. It is emphasized that the system synergy of the educational and museum space modernizes the educational process. In modern conditions, museum pedagogy is a part of the activity not only of museums and educational institutions, but it penetrates gradually into scientific establishments, state institutions and public organizations. The author considers the educational and cultural project on museum pedagogy introduced by the local authorities of Kyiv, the Kyiv Mala Academy of Student Youth and the National Union of Local Lore Researchers of Ukraine.Its purpose is to realize the pedagogical potential of museums in the educational space of Kyiv, by means of museum pedagogy to effectively influence the educational process, to promote the creative abilities of student youth, to form a modern personality as a “man of the museum type” in the conditions of the museum environment.